2004
DOI: 10.1099/mic.0.27122-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of the synthesis of the compatible solute ectoine in the halophilic bacterium Chromohalobacter salexigens DSM 3043T

Abstract: The synthesis of the compatible solute ectoine, mediated by the ectABC gene products, is the main mechanism used by the halophilic bacterium Chromohalobacter salexigens to cope with osmotic stress. Evidence was found that this process is regulated at the transcriptional level. S1 protection analyses performed with RNA extracted from cells grown in minimal medium at low (0?75 M NaCl) or high (2?5 M NaCl) osmolarity suggested the existence of four promoters upstream of ectA. Two of these (PectA1 and PectA2) migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
109
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 55 publications
7
109
0
1
Order By: Relevance
“…It was demonstrated that in C. salexigens and Streptomyces griseus, intracellular levels of ectoine increase in response to high growth temperature (Calderon et al, 2004;Malin and Lapidot, 1996). These findings suggest a role of ectoine as a protectant against the detrimental effects of high temperatures.…”
Section: Ectoine Synthase (Ectc Ec 421108)mentioning
confidence: 69%
See 4 more Smart Citations
“…It was demonstrated that in C. salexigens and Streptomyces griseus, intracellular levels of ectoine increase in response to high growth temperature (Calderon et al, 2004;Malin and Lapidot, 1996). These findings suggest a role of ectoine as a protectant against the detrimental effects of high temperatures.…”
Section: Ectoine Synthase (Ectc Ec 421108)mentioning
confidence: 69%
“…Participation of different transcriptional sigma factors in expression of the ect-genes was not confirmed by an appropriate genetic study. Supplementation of the growth media with ectoine or glycine betaine decreased the transcription of PectA-lacZ and PectB-lacZ (Calderon et al, 2004). Altogether with constitutive ect-genes transcription from PectA and PectB at low osmolarity, this implies an involvement of other transcriptional factors.…”
Section: Ectoine Synthase (Ectc Ec 421108)mentioning
confidence: 83%
See 3 more Smart Citations